Transformational Leadership, Job Performance, and Organizational Citizenship Behavior: Mediating Role of Work Engagement - Novel Idris Abas; Huni Sri Runing Sawitri; Dewita Puspawati (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
Many studies had discussed about organizational behavior such as organizational culture, motivation, organizational commitment and many others topics. However, just few studies that discussed the mediation effect of the organizational behavior variables. Work engagement is one of the important variables in organizational behavior scope. This study proposes and tests a research model that investigates and examine whether work engagement functions as a mediator of the effect of transformational leadership on job performance and OCB. These relationships are assessed through SPSS using Barron & Kenny mediation method. Data are obtained from 97 employees of pharmaceutical company in Indonesia especially Solo Raya and Madiun City. The result shows that work engagement mediates the effect of transformational leadership on job performance. Moreover, this study provides evidence to support our intended hypothesizes, by applying correlation and regression analysis which result have revealed that transformational leadership effects OCB through the mediating effect of work engagement.